An Expansion of Intelligent Systems Complex for Express-Diagnostics and Prevention of Organizational Stress, Depression, and Deviant Behavior on the Basis of the Biopsychosocial Approach; Pattern Recognition and Image Analysis; Vol. 27, No. 4 - Yankovskaya A. E. Anna Efimovna; Kornetov A. N. Aleksandr Nikolaevich; Iljinskikh N. N.; Obukkhovskaya V. B. (2017, 2017)
Title screen